Análise crítica do orçamento participativo do governo autônomo descentralizado do município de Ibarra-Equador - Orbes, Gabriela Ruales (2017)
The main objective of this study of the Participatory Budget (PB) in the “Gobierno Autónomo Descentralizado del Cantón Ibarra” (Imbabura,Ecuador), (Autonomous and Decentralized Government of the Canton Ibarra) is to evaluate to what extend the PB model implemented in the Ibarra canton meets the objectives of articulation between the cantonal government with the organized society and the redistribution public resources. The geographical category of the territory is the basis of the study; weather for the initial reading of the canton, such as the PB, the institutional organization, socialization or public debate, the redistribution of the public resources. Regarding the institutional organization, it was verified that the change of the 2008 Constitution and the rest of the National Legislation changed the PB process, which was already implemented in the canton since the end of the nineties. For this reason it went from a model of standards and local management with its particularities, to a standardized model by the Central Government of national scale. These modifications introduced by the PB made this process an instrument and more exactly, a competence of the GADs throughout the country, facilitating its application from a single standard. However, some of the characteristics and particularities of the local experience were not taken into account, resulting in a more dependent process of the cantonal government and the Central Government. There was no complementarity between local and national development.